Perempuan dan Semer Mendem: Kajian Sejarah, Strategi pemasaran dan Budaya di Kota Palu - Triawati, Komang; Saudo, Fatma; Khotimah, Khusnul (Sasdaya: Gadjah Mada Journal of Humanities, 2023)
The historical background of women in Palu City choosing to sell Semar Mendem stems from culinary businesses related to sticky rice in Central Sulawesi since the 1930s. The introduction of Semar Mendem in 2017 experienced swift popularity among the people of Palu, leading to a substantial increase in demand from 7 to 30 outlets by 2021-2023.This qualitative study explores the marketing strategy of traditional culinary delights in Palu City, emphasizing the historical context of Semar Mendem sales, the evolution of marketing strategies, and the cultural influences surrounding this culinary delight. The research employs a historical approach with a qualitative method involving five stages, focusing on emotional and intellectual closeness. Data collection involves primary and secondary sources, on-site interviews, direct observation, and documentation within Palu City, Central Sulawesi.Four major marketing strategies - product, price, promotion, and place - have contributed to the success of Semar Mendem in Palu City. The study highlights the significance of relationships in business, emphasizing power relations through production, family, and knowledge, illustrating how Semar Mendem has become ingrained as a cultural symbol. The findings illustrate the cultural significance and success of Semar Mendem, portraying its relevance in the historical narrative of Palu City's culinary landscape. Understanding the cultural and historical context of this culinary delight serves as a testimony to preserving traditions and fostering successful marketing strategies for similar local products.